The Ethical Characteristics of Autonomous Robots - Alaieri, Fahad; Vellino, Andre (Université d'Ottawa | University of Ottawa, 2016)
Autonomous robots such as self-driving cars are already able to make decisions that have ethical consequences. As machines develop a greater capacity to perform a greater number of tasks autonomously, people will increasingly need to trust them to make reliable decisions related to their safety, health, and even their lives. Consequently, autonomous social robots of the future will need to be able to make trustworthy ethical computations regarding the consequences of their actions despite the greater cost and complexity of engineering.
Keywords: Ethical Robots; Autonomous Cars